Study on e-Commerce in Croatia: Customers' Preferences - Ines Pečenec; Jovana Zoroja (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Rapid development and growth of Internet facilitate business and transforms today's economies. Nowadays is almost impossible to do business or some other activities without Internet usage. Internet enables transactions among clients and stores, which has positive impact on doing business. E-commerce enhances sales and customers' shopping experience and improves business processes. This paper aims to present and analyze e-commerce usage in Croatia. Empirical research on ecommerce in Croatia was conducted to investigate clients' perception and attitudes toward online shopping. Research results revealed that Croats use ecommerce stores, although they named several difficulties, which influence on their online shopping decisions.
Keywords: L8; L81; L86; 330; e-commerce; Internet; customers; Croatia